Dislocated Tongue Muscle Attachment and Cleft Palate Formation. (April 2016) - Kouskoura, T.; El Fersioui, Y.; Angelini, M.; Graf, D.; Katsaros, C.; Chiquet, M.
In Pierre Robin sequence, a retracted tongue due to micrognathia is thought to physically obstruct palatal shelf elevation and thereby cause cleft palate. However, micrognathia is not always associated with palatal clefting. Here, by using the Bmp7 -null mouse model presenting with cleft palate and severe micrognathia, we provide the first causative mechanism linking the two. In wild-type embryos, the genioglossus muscle, which mediates tongue protrusion, originates from the rostral process of Meckel's cartilage and later from the mandibular symphysis, with 2 tendons positive for Scleraxis messenger RNA. In E13.5 Bmp7- null embryos, a rostral process failed to form, and a mandibular symphysis was absent at E17.5. Consequently, the genioglossus muscle fibers were diverted toward the lingual surface of Meckel's cartilage and mandibles, where they attached in an aponeurosis that ectopically expressed Scleraxis . The deflection of genioglossus fibers from the anterior-posterior toward the medial-lateral axis alters their direction of contraction and necessarily compromises tongue protrusion. Since this muscle abnormality precedes palatal shelf elevation, it is likely to contribute to clefting. In contrast, embryos with a cranial mesenchyme-specific deletion of Bmp7 ( Bmp7 :Wnt1-Cre) exhibited some degree of micrognathia but no cleft palate. In these embryos, a rostral process was present, indicating that mesenchyme-derived Bmp7 is dispensable for its formation. Moreover, the genioglossus appeared normal in Bmp7 :Wnt1-Cre embryos, further supporting a role of aberrant tongue muscle attachment in palatal clefting. We thus propose that in Pierre Robin sequence, palatal shelf elevation is not impaired simply by physical obstruction by the tongue but by a specific developmental defect that leads to functional changes in tongue movements.